Discourses and Practices of Radical Democracy. The 15M movement as a space of mobilization - Candón Mena, José; Montero Sánchez, David; Calle Collado, Ángel (PARTECIPAZIONE E CONFLITTO, 2018)
Social movements are builders of what are known as “grammars of democracy”, that is, values, participatory experiences, political cultures, languages and structures for articulating demands. This article analyses the 15M or indignados (outraged) movement in Spain; a collective action that went beyond classical protests in response to the economic crisis and proposed changes in democratic practices. Social movements, particularly from the 1990s onwards, have focused on democracy as both a means and an end in order to address what they perceive as authoritarian globalization. The article approaches 15M mainly as a space for mobilization articulating the heterogeneity of the movement as well as its effects in Spain (anti-eviction struggles, PAH, social tides, etc.) with a direct reference to the master frame of ’radical democracy’. Methodologically, this work is based upon interviews, focus groups and participant observation conducted from May 2011 to June 2012 during the occupation of public squares and subsequent mobilizations. The text situates this phenomenon in the core of the New Global Movements, and connects it with a decade of similar collective actions in Spain and other parts of the world. Finally, aspects such as the role of the Internet as a tool for and driving force of new models of democracy and the scale of assemblies in relation to deliberative democracy are also discussed.